Sleep disturbances in brain tumors: a narrative review - Liang, Qiang; Hu, Tianyi; Yang, Tong; Pan, Yawen; Spruyt, Karen; Zhang, Xinyan; Li, Qiang (Frontiers in Oncology, 2025)
Individuals with brain tumors are more susceptible to comorbid sleep disturbances, which significantly impair daytime functioning, quality of life, and long-term prognosis. A bidirectional relationship between sleep and brain tumors has been suggested, with sleep disturbances in this population being diverse and multifactorial, stemming from neurotransmitter imbalances, treatment interventions, and comorbidities conditions throughout the disease course. While sleep assessment and intervention guidelines exist for cancer more broadly, specific recommendations for neuro-oncological etiology populations remain limited. As awareness grows regarding the negative impact of poor sleep in patients with brain tumors, there is an urgent need for more targeted research to systematically characterize sleep disturbances and explore therapeutic implications. In this context, we conducted a narrative review current on sleep research in patients with brain tumors.